The vascular flora of Gran Sasso and Monti della Laga National Park (Central Italy) - Conti, Fabio; Bartolucci, Fabrizio (Phytotaxa, 2016)
The National Park of Gran Sasso and Monti della Laga is located in central Italy and covers an area of 143,311 ha, across three administrative regions (Abruzzo, Marche and Lazio). To date, there is not a comprehensive floristic study concernig the Park’s territory but only partial contributions regarding specific taxa or restricted sectors. An annotated checklist of the vascular plant species growing in this territory is here presented, based on field surveys carried out from 1993 to 2015, on extensive analysis of relevant literature and on a review of specimens kept in APP, FI, NAP and RO herbaria. The Park’s flora amounts to 2,642 species and subspecies grouped in 739 genera and 121 families. Two hundred twenty nine taxa are endemic to Italy. Seventy seven taxa are newly recorded for Gran Sasso and Monti della Laga National Park, 83 taxa are not confirmed in recent times and, 57 are doubtuful. The non-native plants amount to 137 taxa. The number of taxa recorded in the Gran Sasso and Monti della Laga National Park is the highest ever found in a protected area of the Mediterranean Basin.